Spinal angiography: Vascular anatomy, technique, indications - Grunwald, I; Thron, A; Reith, W (2001)
The indication for spinal angiography has to be closely set as in case of inadequate handling this procedure bares the risk of paraplegia. In unclear spinal symptoms lasting over a longer periode of time, spinal vascular malformation have to be considered. Spinal vascular malformations are often reversibel, especially if diagnosed early. Diagnostic methods have to include spinal angiography if other non-invasive methods do not lead to results. The main point is to consider spinal vascular malformations in unclear cases.